Materiály k nejstarším dějinám Vojvodova, české obce v severozápadním Bulharsku - Jakoubek, Marek (Lidé města, 2008)
The subject matter of the text is the history of the only Czech village in Bulgaria – Vojvodovo (Northwest Bulgaria, country of Vratsa). The study presents the results of research in Bulgarian archives (The Archive of the Institute of Folklore of the Bulgarian Academy of Sciences, The Archive of the Czechoslovakian Club “T.G. Masaryk” in Sofia, The National Archive, archive of the Vojvodovo Municipality and the archive of the Evangelical Methodist Church “Dr. Long”) realized in 2006 and 2007. Included are four documents. 1) Police report about Czechoslovakian minority in Vojvodovo written in 1934; 2) The account- questionnaire of the foundation of Vojvodovo written by the mayor of the village in 1928 – the year of celebration of 1000 years from the death of Simeon I the Great; 3) The outline of the history of Vojvodovo written by the local scholar Bogdan Nikolov, and 4) The interview about the history of Vojvodovo between Bulgarian ethnologist Vladimir Penčev and the head of the last Czech family in Vojvodovo, Josef Kopřiva.